Delayed adjuvant imatinib in patients with high risk of recurrence of gastrointestinal stromal tumor after radical surgery: a retrospective cohort study - Qianyi, Wan; Mei, Xu; Rui, Zhao; Yong, Wang; Yutao, Wu; Xiaoding, Shen; Xiaoting, Wu (Journal of cancer research and clinical oncology, 2022)
Purpose To investigate the impact of delayed adjuvant imatinib on GIST patients with high risk of recurrence. Method Adult GIST patients were retrospectively collected from our hospital between 2011 and 2018, and patients having high risk of recurrence were included for subsequent analyses. The primary endpoint was recurrence-free survival (RFS). Results According to the interval between the radical surgery and the beginning of adjuvant imatinib, 222 patients were divided into three groups: group A (≤ 2 months, n = 41), group B (2–≤ 4 months, n = 113), and group C (4–≤ 6 months, n = 68). Univariate, multivariate, and survival analyses all showed that patients in group A had significantly more favorable RFS than those in group C but not group B, and patients taking adjuvant imatinib for over 12 months were also associated with longer RFS comparing to adjuvant imatinib of ≤ 12 months. When stratified by the duration of adjuvant imatinib, no significant differences were found in RFS among groups A, B, and C for adjuvant imatinib of ≤ 12 months. While for adjuvant imatinib of over 12 months, both groups A and B had significantly more favorable RFS than group C, and no significant difference in RFS was found between group A and B. Conclusion Delayed postoperative adjuvant imatinib for over 4 months in patients with high risk of recurrence of GIST may lead to worse RFS, and longer treatment with shorter delay has best results.